Health of students in modern environmental conditions and innovative technologies. - Losik T. N.; Sorokin U.S; Dolinnyj U.A (Kharkov National Pedagogical University, 2011)
It is shown the row of the phenomena which negatively influence not only on a health man but also on his professional capacity: detraining of an organism through the lack of motive activity, tense emotional state of man in the process of his everyday work, negative influencing of environment and innovative technologies. The analysis of publications which examine influence of environment and innovative technologies on the state of health of man is presented. The system of organism is certain, feel like negative influence of environment and innovative technologies. It is set that an environment is indissolubly related to the man, which is the active object of nature.